POLITICAL AND IDENTITY REPRESENTATION IN WARFARE (2025): VISUALIZING MIDDLE EASTERN MUSLIMS IN POST-9/11 AMERICAN CINEMA - Adha, Isa Ardina; Prihatika, Yusrina Dinar Prihatika (Journal of Social Politics and Governance (JSPG), 2025)
This study examines how Warfare (2025), a post-9/11 American war film, represents the political and identity positioning of Middle Eastern Muslims. Using Edward Said’s Orientalism, Homi K. Bhabha’s Postcolonial Theory, and qualitative textual–cinematic analysis, the research explores how the film frames American military subjectivity while minimizing the visibility and agency of Middle Eastern Muslim characters. The study aims to understand how the film’s narrative structure and visual choices shape ideological meaning and reinforce familiar patterns of representation in war cinema. The findings show that the film employs a subtle but persistent strategy of erasure, portraying Iraqi civilians only in brief, backgrounded moments without dialogue, cultural detail, or narrative importance. In contrast, the emotional and psychological experiences of U.S. soldiers are depicted with depth and consistency, encouraging viewers to align with American perspectives. These representational patterns ultimately reaffirm Orientalist hierarchies and support a broader legitimization of U.S. militarism within contemporary cinematic storytelling.